PORNOGRAFI DI MEDIA MASSA INDONESIA - Wijaya, Sri Herwindya Baskara (KOMUNITAS)
Ethic actually is a dialog between freedom and responbility, between destination and methods to get it. Although there are regulation toregulate about proffesion ethic, but media user often donât follow it. We can see from news in mass media which is saw not suitableÂ  withÂ  ethicÂ  codeÂ  inÂ  regulation.Â  OneÂ  ofÂ  itÂ  isÂ  connectedÂ  withÂ  pornography publication in mass media. The interest to get maximal capital is one cause of it. The effect, public become victims from it especially cildren and adolescent.Â  Based on the introduction,Â  theÂ  issuesÂ  raisedÂ  inÂ  thisÂ  articleÂ  isÂ  howÂ  theÂ  imageÂ  ofÂ  pornographic publicationsÂ  inÂ  massÂ  mediaÂ  inÂ  IndonesiaÂ  areÂ  consideredÂ  toÂ  violateÂ  theÂ  formal journalistic code of ethics applicable. The expected goals of writing this article is to find a picture pornographic publications in mass media in Indonesia are considered to violate the formal journalistic code of ethics applicable.Keywords : Ethic, regulation, pornograph, mass media, capital